Adhesive material for quantum current sensor package, sensor and process of making
Patent Information
- Application Number
- CN202610906996.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-06-23
AI Technical Summary
[0052]上述面向量子电流传感器封装的粘接材料及其梯度固化工艺、传感器及其制备方法,提供第一基材和第二基材;配制得到热膨胀系数目标值呈梯度变化的多种浆料;每种浆料均包括陶瓷基体相、纳米填料调控相和纤维增强相,不同浆料中的材料配比不同,呈梯度变化的热膨胀系数目标值是根据第一基材的热膨胀系数与第二基材的热膨胀系数之间的差异确定的;在第一基材的界面上按照梯度变化逐层涂布多种浆料,形成粘接层;其中,每涂布一层浆料后进行预固化处理,并在相邻层之间形成组分互扩散的过渡区;在粘接层上覆盖第二基材,形成复合粘接结构;其中,陶瓷基体相包括磷酸铝,或者,陶瓷基体相包括磷酸铝和氧化铝;纳米填料调控相包括纳米氮化铝、纳米氮化硼以及纳米二氧化硅中的至少两种;纤维增强相包括短切碳纤维和短切氧化铝纤维中的至少一种。通过上述方式,使得最终形成的粘接层在厚度方向上具有连续或阶梯式变化的热膨胀系数,能够使粘接层靠近第一基材一侧的热膨胀系数与该基材良好匹配,靠近第二基材一侧的热膨胀系数与该基材良好匹配,中间层则实现平滑过渡,从而大幅减小相邻层间的热膨胀系数突变,显著降低界面热应力,有效抑制因热循环引起的粘接层开裂、芯片翘曲及器件失效,显著提高异质材料封装结构的热循环可靠性和服役寿命。通过逐层涂布、预固化处理以及形成过渡区,在保持多层梯度结构有序构建的前提下,消除层间界面,实现成分与性能的准连续过渡,从而大幅降低热应力并提高结构可靠性。陶瓷基体相包括磷酸铝或磷酸铝与氧化铝的组合,该陶瓷基体可在较低温度下完成固化,避免对热敏感元件造成损伤。同时,纳米填料调控相中的纳米氮化铝、纳米氮化硼等具有高本征导热率,纤维增强相中的短切碳纤维也具有优异的导热性能,两者的协同作用使粘接层具备良好的厚度方向导热能力,有利于快速散除芯片工作产生的热量,降低结温,延长器件使用寿命。通过梯度配比的三相复合粘接层设计,实现了热膨胀系数在多界面体系中的柔性匹配,同时兼顾了低应力、高导热、高韧性和对敏感元件的低温工艺兼容性,为高可靠性量子传感器及其他异质集成器件的封装提供了有效的技术方案。
Smart Images

Figure CN122445290B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of measurement device packaging technology, and in particular to an adhesive material for packaging quantum current sensors, its gradient curing process, the sensor, and its fabrication method. Background Technology
[0002] As quantum precision measurement technology accelerates its transition from basic laboratory research to engineering applications, quantum current sensors based on diamond NV centers have become a core candidate for next-generation high-precision current metering devices due to their unique advantages in sensitivity, bandwidth, and electromagnetic interference resistance. However, the engineering application of quantum current sensors places extremely stringent requirements on the reliability of device packaging: the core of the sensor is composed of multiple heterogeneous materials stacked together, including a diamond sensing chip, a silicon-based ASIC processing chip, an aluminum nitride (AlN) or aluminum oxide (Al2O3) ceramic packaging substrate, and a copper or tungsten-copper alloy heat sink. The coefficients of thermal expansion (CTE) of each layer differ significantly (approximately 1.0 × 10⁻⁶ for diamond). -6 / ℃, silicon approximately 2.6×10 -6 / ℃, aluminum nitride ceramic approximately 4.5×10 -6 / ℃, copper approximately 17×10 -6 When a device cycles within a wide temperature range of -40℃ to 85℃, the CTE mismatch at adjacent interfaces will generate enormous thermal stress, leading to adhesive layer cracking, chip warping, and even device failure. Therefore, developing an adhesive material that can achieve flexible CTE matching between multiple interfaces while possessing high thermal conductivity and excellent mechanical properties is a core technological requirement for the reliability of quantum current sensor packaging.
[0003] Regarding this issue, there has been some technological accumulation in the field of low thermal stress bonding of heterogeneous materials both domestically and internationally. However, existing solutions still have the following significant shortcomings when applied to quantum sensor packaging scenarios:
[0004] First, traditional epoxy-based adhesives have excessively high and uncontrollable coefficients of thermal expansion (CTE). Epoxy resin-based adhesives, widely used in conventional electronic packaging, typically have a coefficient of thermal expansion of 60 × 10⁻⁶. -6 / ℃-40×10 -6 The temperature is around 180℃, which is still much higher than that of diamond and silicon-based materials. In addition, the glass transition temperature (Tg) of epoxy resin generally does not exceed 180℃. After high-temperature curing, stress rebound is a serious problem, and the mechanical properties degrade significantly after humid heat aging, which cannot meet the requirements of quantum sensors for long-term service of more than 15 years.
[0005] Second, metal bonding processes such as silver sintering cause additional damage to quantum sensitive elements. In recent years, nano-silver sintering technology has gained widespread attention in power electronic device packaging due to its high thermal conductivity and high reliability. However, this technology requires high-temperature and high-pressure sintering conditions of 250℃~300℃. Such high process temperatures can lead to zero-phonon line broadening, coherence time T2 degradation, and even charge state transitions (NV) in diamond NV centers. - →NV 0 This significantly affects the sensitivity and signal-to-noise ratio of the quantum sensor. Meanwhile, the CTE of the silver sintered layer is approximately 19 × 10⁻⁶. -6 At ℃, there is still a nearly 20-fold CTE mismatch between the diamond and the thermal cycling reliability, resulting in limited improvement.
[0006] Third, existing ceramic-based adhesives suffer from high brittleness and poor interfacial wettability. While inorganic ceramic-based adhesives (such as phosphate-based and silicate-based adhesives) have the inherent advantage of low CTE, their inherent brittleness makes them highly susceptible to through-crack formation under temperature cycling loads. Furthermore, pure ceramic-based adhesives typically exhibit wetting angles greater than 60° on diamond and silicon surfaces, with interfacial bond strengths less than 5 MPa, making them prone to interfacial debonding under thermal stress. Existing literature reports improving wettability by adding organic additives; however, the introduction of organic components increases the overall CTE, creating a performance incompatibility dilemma.
[0007] Fourth, single-scale fillers struggle to simultaneously achieve both CTE regulation and crack prevention. Current research has explored adding micron-sized ceramic particles (such as alumina and silicon carbide) to polymer or ceramic matrices to reduce CTE; however, these micron-sized particles tend to create stress concentration points within the matrix, potentially becoming crack initiation sites. While using nanoparticles alone can improve dispersibility, they face severe agglomeration problems at high filler ratios (>50 vol%), leading to numerous pores and defects within the material, weakening its mechanical strength and thermal conductivity. Maintaining uniform dispersion of nanofillers while achieving high filler ratios remains a bottleneck that current technologies have failed to effectively address.
[0008] Fifth, there is a lack of systematic design methods for multi-interface CTE gradient transitions. The packaging structure of quantum current sensors contains at least several heterogeneous interfaces, such as diamond / adhesive layer, adhesive layer / silicon, silicon / adhesive layer, adhesive layer / ceramic substrate, ceramic substrate / adhesive layer, and adhesive layer / metal base. Existing technologies typically design adhesive materials for single interfaces, neglecting the systematic gradient matching requirement of CTE between multiple interfaces. When the thermal stress at one interface is reduced, the stress may transfer and concentrate to adjacent interfaces, resulting in insignificant improvement in overall reliability. Currently, there is a lack of an integrated solution that co-designs nanofiller ratios, fiber orientation, curing processes, and multi-interface gradient structures.
[0009] Sixth, the curing process lacks sophisticated methods for controlling residual stress. The curing process of adhesive materials itself generates chemical shrinkage stress and thermal shrinkage stress. The residual stress formed by the superposition of these two stresses is an important cause of interfacial debonding in the early stages of service. Traditional isothermal curing or stepped temperature curing processes lack quantitative control over the curing kinetics of ceramic matrix composites and cannot adjust the temperature and pressure curves in real time according to changes in the material composition gradient, resulting in asynchronous curing shrinkage between different layers and accumulation of interlayer residual stress. Summary of the Invention
[0010] Based on this, it is necessary to address the above-mentioned technical problems by providing an adhesive material for quantum current sensor packaging, its gradient curing process, the sensor itself, and its fabrication method. Through the design of a gradient-ratio three-phase composite adhesive layer, flexible matching of the coefficient of thermal expansion in a multi-interface system is achieved, while taking into account low stress, high thermal conductivity, high toughness, and low-temperature process compatibility with sensitive elements. This provides an effective technical solution for the packaging of high-reliability quantum sensors and other heterogeneous integrated devices.
[0011] In a first aspect, this application provides a gradient curing process for an adhesive material, comprising:
[0012] Provide a first substrate and a second substrate;
[0013] Multiple slurries with gradient-varying target values of thermal expansion coefficient were prepared. Each slurry included a ceramic matrix phase, a nanofiller regulating phase, and a fiber reinforcing phase. The material ratios in different slurries were different, and the gradient-varying target values of thermal expansion coefficient were determined based on the difference between the thermal expansion coefficients of the first substrate and the second substrate.
[0014] Multiple slurries are applied layer by layer at the interface of the first substrate in a gradient manner to form an adhesive layer; wherein, after each layer of slurry is applied, a pre-curing treatment is performed, and a transition zone for component interdiffusion is formed between adjacent layers;
[0015] A second substrate is covered on the adhesive layer to form a composite adhesive structure;
[0016] The ceramic matrix phase includes aluminum phosphate, or the ceramic matrix phase includes aluminum phosphate and alumina; the nanofiller regulating phase includes at least two of nano-aluminum nitride, nano-boron nitride and nano-silica; the fiber reinforcing phase includes at least one of chopped carbon fibers and chopped alumina fibers.
[0017] In one embodiment, the process further includes:
[0018] When applying any layer of slurry, a doctor blade is used for application, or the slurry placed at the center of the interface of the first substrate is radially spread under the action of centrifugal force by rotational coating.
[0019] In one embodiment, the step of preparing any kind of slurry includes:
[0020] Based on the material ratio corresponding to the current target value of thermal expansion coefficient, obtain the corresponding precursor solution, nanofiller and fiber material;
[0021] The nanofiller was dry-mixed to obtain a pre-dispersed powder;
[0022] The pre-dispersed powder is mixed into the precursor solution and dispersed by wet ball milling to obtain a ball mill slurry;
[0023] The ball-milled slurry was vacuum-stirred and degassed to obtain a matrix slurry;
[0024] Fiber material is added to the matrix slurry, and then stirred and vacuum degassed in sequence to obtain the prepared slurry.
[0025] In one embodiment, before preparing various slurries with target coefficients of thermal expansion varying in a gradient, the process further includes:
[0026] Nano-aluminum nitride was ultrasonically dispersed in anhydrous ethanol, then a silane coupling agent was added, followed by heating, stirring, and reflux treatment. After centrifugation, washing, and vacuum drying, surface-modified nano-aluminum nitride was obtained; or...
[0027] Nano-sized boron nitride is oxidized in concentrated nitric acid to introduce oxygen-containing functional groups onto its surface; then, the oxidized boron nitride is coated with a dopamine-inspired coating in an alkaline buffer solution to form a polydopamine surface-modified layer, thus obtaining surface-modified boron nitride nano-nitride; or...
[0028] Nano-silica was dispersed in an organic solvent, and an aluminate coupling agent was added. The mixture was then heated and stirred to react. After filtration and drying, surface-modified nano-silica was obtained.
[0029] In one embodiment, the ceramic matrix phase comprises aluminum phosphate and alumina; the mass percentage of aluminum phosphate in the ceramic matrix phase is 35%~45%, and the mass percentage of alumina is 55%~65%.
[0030] The nanofiller regulating phase includes nano-aluminum nitride, nano-boron nitride, and nano-silica; the volume percentage of nano-aluminum nitride in the nanofiller regulating phase is 35%~65%, the volume percentage of nano-boron nitride is 20%~35%, and the volume percentage of nano-silica is 15%~30%.
[0031] The fiber-reinforcing phase includes chopped carbon fibers and chopped alumina fibers; the volume percentage of chopped carbon fibers in the fiber-reinforcing phase is 60%~75%, and the volume percentage of chopped alumina fibers is 25%~40%.
[0032] In each slurry, the volume percentage of the nanofiller-controlled phase is 30% to 55%, and the volume percentage of the fiber-reinforced phase is 5% to 15%.
[0033] In one embodiment, the first substrate includes any one of a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer. Before forming the adhesive layer, multiple pastes are applied layer by layer at the interface of the first substrate in a gradient manner.
[0034] The interface of the metal base layer is degreased by electrochemical alkaline washing and then anodized in an acidic solution to form an oxide layer with a microporous structure, resulting in a pretreated metal base layer; or...
[0035] The interface of the ceramic substrate layer is sandblasted to obtain a pretreated ceramic substrate layer; or...
[0036] A silanol layer is formed at the interface of the silicon chip layer, and a self-assembled monolayer is coated thereon to obtain a pretreated silicon chip layer; or,
[0037] The interface of the diamond layer is treated with oxygen plasma to introduce oxygen-containing functional groups into the interface of the diamond layer, resulting in a pretreated diamond layer.
[0038] Secondly, this application also provides an adhesive material for packaging quantum current sensors, the adhesive material comprising a ceramic matrix phase, a nanofiller regulating phase, and a fiber-reinforced phase;
[0039] The ceramic matrix phase includes aluminum phosphate and alumina; the mass percentage of aluminum phosphate in the ceramic matrix phase is 35%~45%, and the mass percentage of alumina is 55%~65%.
[0040] The nanofiller regulating phase includes nano-aluminum nitride, nano-boron nitride, and nano-silica; the volume percentage of nano-aluminum nitride in the nanofiller regulating phase is 35%~65%, the volume percentage of nano-boron nitride is 20%~35%, and the volume percentage of nano-silica is 15%~30%.
[0041] The fiber-reinforcing phase includes chopped carbon fibers and chopped alumina fibers; the volume percentage of chopped carbon fibers in the fiber-reinforcing phase is 60%~75%, and the volume percentage of chopped alumina fibers is 25%~40%.
[0042] In each slurry, the volume percentage of the nanofiller-controlled phase is 30% to 55%, and the volume percentage of the fiber-reinforced phase is 5% to 15%.
[0043] Thirdly, this application also provides a sensor, including a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer;
[0044] Composite bonding structures formed by the process described in the first aspect above are respectively provided between the metal base layer and the ceramic substrate layer, between the ceramic substrate layer and the silicon chip layer, and between the silicon chip layer and the diamond layer.
[0045] In the composite bonding structure, the first substrate and the second substrate correspond to one of the two adjacent layers of the sensor, respectively.
[0046] Fourthly, this application also provides a method for fabricating a sensor, comprising:
[0047] It provides a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer;
[0048] Using the process described in the first aspect above, adhesive layers are formed between the metal base layer and the ceramic substrate layer, between the ceramic substrate layer and the silicon chip layer, and between the silicon chip layer and the diamond layer, respectively, to obtain a sensor that is connected as a whole.
[0049] In one embodiment, the method further includes:
[0050] After any adhesive layer is formed, the formed adhesive layer is subjected to a layer co-curing treatment; or,
[0051] After all adhesive layers are formed, all adhesive layers are subjected to component-level co-curing.
[0052] The aforementioned adhesive material for quantum current sensor encapsulation, its gradient curing process, the sensor, and its fabrication method provide a first substrate and a second substrate; multiple slurries with gradient-varying target values of thermal expansion coefficients are prepared; each slurry includes a ceramic matrix phase, a nanofiller regulating phase, and a fiber reinforcing phase, with different material ratios in different slurries, and the gradient-varying target value of the thermal expansion coefficient is determined based on the difference between the thermal expansion coefficients of the first substrate and the second substrate; multiple slurries are applied layer by layer at the interface of the first substrate according to the gradient change to form an adhesive layer; wherein, after each layer of slurry is applied, a pre-curing treatment is performed, and a transition zone for component interdiffusion is formed between adjacent layers; the second substrate is covered on the adhesive layer to form a composite adhesive structure; wherein, the ceramic matrix phase includes aluminum phosphate, or the ceramic matrix phase includes aluminum phosphate and alumina; the nanofiller regulating phase includes at least two of nano-aluminum nitride, nano-boron nitride, and nano-silica; and the fiber reinforcing phase includes at least one of chopped carbon fibers and chopped alumina fibers. Through the above methods, the final adhesive layer exhibits a continuously or stepped coefficient of thermal expansion in its thickness direction. This ensures a good match between the thermal expansion coefficient of the adhesive layer near the first substrate and that of the second substrate, while achieving a smooth transition in the intermediate layers. This significantly reduces abrupt changes in the thermal expansion coefficient between adjacent layers, substantially lowers interfacial thermal stress, effectively suppresses adhesive layer cracking, chip warpage, and device failure caused by thermal cycling, and significantly improves the thermal cycling reliability and service life of heterogeneous material packaging structures. By layer-by-layer coating, pre-curing, and the formation of transition zones, the interlayer interfaces are eliminated while maintaining the orderly construction of the multi-layer gradient structure, achieving a quasi-continuous transition in composition and performance, thereby significantly reducing thermal stress and improving structural reliability. The ceramic matrix phase includes aluminum phosphate or a combination of aluminum phosphate and alumina. This ceramic matrix can be cured at lower temperatures, avoiding damage to heat-sensitive components. Meanwhile, the nano-aluminum nitride and nano-boron nitride in the nanofiller-controlled phase possess high intrinsic thermal conductivity, while the short-cut carbon fibers in the fiber-reinforced phase also exhibit excellent thermal conductivity. The synergistic effect of these two components gives the adhesive layer good thermal conductivity in the thickness direction, which is beneficial for rapidly dissipating heat generated during chip operation, reducing junction temperature, and extending device lifespan. Through a gradient-ratio three-phase composite adhesive layer design, flexible matching of the coefficient of thermal expansion in a multi-interface system is achieved, while also considering low stress, high thermal conductivity, high toughness, and low-temperature process compatibility with sensitive components. This provides an effective technical solution for the packaging of high-reliability quantum sensors and other heterogeneous integrated devices. Attached Figure Description
[0053] To more clearly illustrate the technical solutions in the embodiments of this application or related technologies, the drawings used in the description of the embodiments of this application or related technologies will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0054] Figure 1 This is a schematic diagram of the gradient curing process of the adhesive material in one embodiment;
[0055] Figure 2 This is a schematic diagram of the stacked architecture in a sensor;
[0056] Figure 3 A schematic diagram of a multi-interface CTE gradient matching structure for diamond-silicon chip-ceramic substrate-metal base;
[0057] Figure 4 This is a schematic diagram of the microstructure of nanofillers (AlN, BN, SiO2) and fiber-reinforced phases in a ceramic matrix.
[0058] Figure 5 A complete process flow diagram for the fabrication of composite adhesive structures and sensors;
[0059] Figure 6 A flow chart of gradient curing process and temperature-pressure-curing degree coordination control curve;
[0060] Figure 7 The figure shows the comparative test results of the present invention and the traditional solution in terms of thermal cycling reliability. Detailed Implementation
[0061] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0062] It should be noted that the terms "first," "second," etc., used in this application can be used to describe various elements, but these elements are not limited by these terms. These terms are only used to distinguish the first element from the second element. The terms "comprising" and "having," and any variations thereof, used in this application, are intended to cover non-exclusive inclusion. The term "multiple" used in this application refers to two or more. The term "and / or" used in this application refers to one of the embodiments, or any combination of multiple embodiments.
[0063] In one exemplary embodiment, such as Figure 1As shown, a gradient curing process for an adhesive material is provided, comprising:
[0064] Step 102: Provide a first substrate and a second substrate.
[0065] In this embodiment, the first substrate and the second substrate are two solid components that need to be connected to each other. The first substrate and the second substrate are made of different materials, and due to the difference in their coefficients of thermal expansion (CTE), thermal mismatch stress will be generated during temperature changes. This embodiment uses a subsequent gradient adhesive layer to mitigate this stress.
[0066] Exemplary examples show that the first substrate and the second substrate can be independently selected from any of the following materials: diamond, silicon, ceramics (e.g., aluminum nitride ceramics, alumina ceramics), metals (e.g., copper, tungsten copper alloys, Kovar alloys), and glass. In a preferred application scenario of the present invention, the first substrate is a diamond-sensitive chip and the second substrate is a silicon-based ASIC chip; or the first substrate is a silicon chip and the second substrate is an aluminum nitride ceramic substrate; or the first substrate is a ceramic substrate and the second substrate is a copper or tungsten copper alloy heat sink. The above list is not limiting, and those skilled in the art can select any two substrates to be bonded according to actual packaging requirements.
[0067] The surfaces of the first and second substrates can be untreated raw surfaces, or they can be pretreated as needed to improve the interfacial bonding strength with the adhesive layer.
[0068] After providing the first and second substrates, it is necessary to obtain their coefficients of thermal expansion (CTE) or the difference between them. This difference serves as the target for subsequent design of the adhesive layer gradient. For example, based on the CTE A of the first substrate and the CTE B of the second substrate, the target CTE value of the adhesive layer near the first substrate should approach A, and the target CTE value near the second substrate should approach B. The CTE values of intermediate layers then transition from A to B according to a certain gradient rule (such as linear, exponential, or stepwise variation). This gradient design aims to match the CTE of each local area of the adhesive layer with that of the adjacent substrate or adjacent sublayer, thereby dispersing thermal stress throughout the thickness direction of the adhesive layer and avoiding stress concentration.
[0069] Step 104: Prepare a variety of slurries with a gradient of target values for thermal expansion coefficients; each slurry includes a ceramic matrix phase, a nanofiller regulating phase, and a fiber reinforcing phase. The material ratios in different slurries are different, and the target values for thermal expansion coefficients with gradient changes are determined based on the difference between the thermal expansion coefficients of the first substrate and the second substrate.
[0070] In this process, after providing a first substrate and a second substrate and determining the difference in their coefficients of thermal expansion (CTE), various slurries are designed and formulated based on this difference. Each slurry has a different target CTE value, and these target values vary continuously or in a stepped gradient along the thickness direction of the adhesive layer. Each slurry contains a ceramic matrix phase, a nanofiller regulating phase, and a fiber reinforcing phase, with different proportions of the three phases in different slurries to achieve different target CTE values.
[0071] The ceramic matrix phase refers to the precursor material that forms an inorganic ceramic network after curing. The nanofiller regulating phase refers to nanoscale particles used to reduce the coefficient of thermal expansion and improve the thermal conductivity of the composite material. The multidimensional reinforcing phase includes chopped fibers, used to improve the fracture toughness of the material and provide additional CTE regulation capability.
[0072] For example, the target CTE value of each sublayer of the adhesive layer is determined based on the thermal expansion coefficient A of the first substrate and the thermal expansion coefficient B of the second substrate. Assume the adhesive layer contains N sublayers (N≥2), and the target CTE value transitions from A to B linearly or stepwise from the first layer closest to the first substrate to the Nth layer closest to the second substrate. To control thermal stress, the CTE jump between adjacent sublayers should not exceed 2 × 10⁻⁶. -6 / ℃. When there is a large difference between A and B, a smooth transition can be achieved by increasing the number of sublayers (e.g., 4-6 layers).
[0073] For example, this embodiment uses a method that combines the improved Turner model with the Schappery upper and lower bound models for CTE prediction and formulation design.
[0074] For the particle-reinforced portion, the effective CTE is calculated using the Turner model, and the expression is:
[0075] ;
[0076] in, For the CTE of the i-th phase, Let be the bulk modulus of the i-th phase. This represents the volume fraction (i.e., volume percentage) of the i-th phase. For the four-phase system of the example (aluminum phosphate matrix, nano-AlN, nano-BN, nano-SiO2), the breakdown is as follows:
[0077] ;
[0078] For the fiber-reinforced portion, the Schappery model is used to calculate the contribution of fiber orientation to the effective CTE. For randomly oriented chopped fiber composites, the in-plane effective CTE is:
[0079] ;
[0080] in, This represents the fiber volume fraction. For fiber axial CTE, This refers to the axial elastic modulus of the fiber. The equivalent elastic modulus of the matrix. The fiber length efficiency factor. This represents the fiber orientation efficiency factor. The fiber length efficiency factor is expressed as:
[0081] ;
[0082] ;
[0083] in, The matrix shear modulus. Where is the fiber radius, It is half the distance between fibers. This represents the fiber length.
[0084] Fiber orientation efficiency factor Determined based on the actual distribution of fibers within the adhesive layer: for in-plane random orientation distribution For directional arrangement, For a three-dimensional random distribution, .
[0085] Based on the above models, the final effective CTE expression for composite adhesive materials is:
[0086] ;
[0087] in, This is a CTE correction term caused by interfacial thermal resistance. The CTE correction term is for residual porosity, and both were obtained through experimental calibration. For the material provided in this embodiment, when the porosity is controlled below 2%, Less than 0.1×10 -6 / ℃, which is negligible.
[0088] By adjusting the nanofiller ratio and fiber volume fraction, the effective CTE of the composite adhesive material can be increased to 1.5 × 10⁻⁶. -6 / ℃ to 8.0×10 -6 Continuously adjustable within a / ℃ range. In one optional implementation, the following key CTE matching nodes are specifically implemented:
[0089] Near the diamond side (CTE target value 1.5 to 2.5 × 10⁻⁶) -6 / ℃): The total amount of nanofiller is 55 vol%, of which BN accounts for 35%, SiO2 accounts for 30%, AlN accounts for 35%, and carbon fiber accounts for 15 vol% and is oriented in-plane.
[0090] Closest to the silicon chip side (CTE target value 2.5 to 3.5 × 10⁻⁶) -6 / ℃): The total amount of nanofiller is 45 vol%, of which AlN accounts for 45%, BN accounts for 25%, SiO2 accounts for 30%, and carbon fiber accounts for 10 vol% with in-plane random orientation.
[0091] Near the ceramic substrate side (CTE target value 4.0 to 5.5 × 10⁻⁶) -6 / ℃): Total amount of nanofiller 35 vol%, of which AlN accounts for 60%, BN accounts for 20%, SiO2 accounts for 20%, and alumina fiber 8 vol% is randomly oriented in plane.
[0092] Near the metal base side (CTE target value 6.0 to 8.0 × 10⁻⁶) -6 / ℃): The total amount of nanofiller is 30 vol%, mainly AlN (accounting for 65%), with a small amount of BN and SiO2, and the fiber content is 5 vol%, which is randomly distributed in three dimensions.
[0093] Among them, reference Figure 2 The quantum current sensor packaging structure comprises a multi-layered architecture consisting of diamond / adhesive layer / silicon chip / adhesive layer / ceramic substrate / adhesive layer / metal base, with a stepped distribution of CTE between each layer. By designing the adhesive material as a gradient structure with gradually changing components, the adhesive layer itself becomes a CTE transition layer, achieving flexible mechanical matching between adjacent materials.
[0094] The design principle of gradient structures is based on the thermoelasticity criterion of minimizing interfacial stress. For a bimaterial bonded joint, the thermal stress at the interface during cooling is:
[0095] ;
[0096] in For poor CTE, The change in temperature and The elastic modulus of two adjacent layers. and This refers to the thickness of two adjacent layers. As can be seen from the above, reducing... It is the most direct and effective way to reduce interfacial thermal stress.
[0097] Therefore, in this embodiment, gradient layers are designed independently for the three bonding locations in the quantum current sensor's "diamond-silicon chip-ceramic substrate-metal base" stacked architecture—bonding location I (between diamond and silicon chip), bonding location II (between silicon chip and ceramic substrate), and bonding location III (between ceramic substrate and metal base). This ensures that the CTE inside each bonding location transitions continuously from top to bottom, and that the CTEs at the upper and lower ends of the bonding location are close to their adjacent substrates.
[0098] Along the entire stacked architecture, four representative transition CTEs are used on the adjacent surfaces of the four substrates (see Appendix). Figure 3 From the diamond side to the metal base side, they are as follows:
[0099] First gradient layer (diamond adjacent surface): CTE = 1.8 × 10 -6 / ℃, thickness 20-30μm, formulation is high BN content (35vol%BN+30vol%SiO2+35%AlN) + carbon fiber directional arrangement (15vol%), aluminum phosphate accounts for 35% in the matrix;
[0100] Second gradient layer (silicon chip adjacent surface): CTE = 3.0 × 10 -6 / ℃, thickness 15-25μm, formulation is medium filler content (45vol%AlN+25vol%BN+30vol%SiO2) + carbon fiber in-plane random orientation (10vol%), aluminum phosphate accounts for 40% in matrix;
[0101] Third gradient layer (adjacent surface of ceramic substrate): CTE = 5.0 × 10 -6 / ℃, thickness 20-30μm, formulation is low filler content (60vol%AlN+20vol%BN+20vol%SiO2) + alumina fiber in-plane random orientation (8vol%), aluminum phosphate accounts for 45% in the matrix;
[0102] Fourth gradient layer (adjacent surface to metal base): CTE = 7.5 × 10 -6 / ℃, thickness 25-35μm, the formula is AlN as the main filler (65vol%AlN + a small amount of BN and SiO2) + a small amount of fiber three-dimensional random distribution (5vol%), and the aluminum phosphate accounts for 45% of the matrix.
[0103] The four gradient layers mentioned above are not stacked simultaneously in the same bonding location. Instead, they serve as representative transition CTEs for the four adjacent substrate surfaces. They are selected by the three bonding locations according to the rule of "taking two adjacent layers as the two ends of this location". The specific configuration is as follows:
[0104] (a) Bonding location I (diamond / silicon chip): The diamond side uses a first gradient layer (CTE=1.8×10⁻⁶).-6 / ℃), a second gradient layer (CTE=3.0×10) is used on one side of the silicon chip. -6 / ℃), the two layers are continuously connected by an interlayer cross-permeability zone, and a CTE = 2.4 × 10 is inserted if necessary. -6 The internal sublayers at / ℃ ensure that the CTE jump variable between any adjacent sublayers does not exceed 2×10. -6 / ℃, the total thickness at this bonding location is 40-55μm;
[0105] (b) Bonding Location II (Silicon Chip / Ceramic Substrate): A second gradient layer (CTE=3.0×10⁻⁶) is used on the silicon chip side. -6 / ℃), a third gradient layer (CTE=5.0×10) is used on one side of the ceramic substrate. -6 / ℃), a CTE = 4.0 × 10 can be inserted between the two layers. -6 The inner sublayer at / ℃ has a total thickness of 40-55μm at this bonding location;
[0106] (c) Bonding location III (ceramic substrate / metal base): A third gradient layer (CTE=5.0×10) is used on one side of the ceramic substrate. -6 / ℃), the metal base uses a fourth gradient layer on one side (CTE=7.5×10). -6 / ℃), a CTE = 6.3 × 10 can be inserted between the two layers. -6 The inner sublayer at / ℃ has a total thickness of 50-65μm at this bonding location.
[0107] Appendix Figure 3 The four gradient layers (CTEs of 1.8, 3.0, 5.0, and 7.5 × 10⁻⁶) arranged from top to bottom along the stacking direction are shown in the diagram. -6 / ℃) is a summary diagram of the representative transition CTE of the four substrate adjacent surfaces in the entire stack direction; the three bonding positions are taken from top to bottom, and the two adjacent layers are taken as the boundary CTE of the two ends of the bonding layer at this position.
[0108] Step 106: Apply multiple slurries layer by layer on the interface of the first substrate according to a gradient to form an adhesive layer; wherein, after each layer of slurry is applied, a pre-curing treatment is performed, and a transition zone for component interdiffusion is formed between adjacent layers.
[0109] In this process, after preparing a series of slurries with target values for gradient thermal expansion coefficients, these slurries are applied layer by layer to the bonding interface of the first substrate in order from the side closest to the first substrate to the side furthest from the first substrate, forming a bonding layer with a multi-layer structure.
[0110] Each layer of slurry applied forms a gradient layer, as shown in the reference. Figure 3The continuous transition of CTE between each gradient layer is achieved through the interlayer cross-penetration zone. That is, after two adjacent gradient layers are coated, before they are fully gelled, the interdiffusion of components to a depth of about 3 to 5 μm occurs in the interface area by controlling the standing time, forming a transition zone with a continuous and gradual change in CTE, thus avoiding abrupt changes in interlayer interface stress.
[0111] The overall equivalent thermal stress of a multilayer gradient structure can be calculated using laminate theory. For an adhesive system containing an N-layer gradient structure, the thermal response of each layer satisfies:
[0112] ;
[0113] in, For the in-plane stiffness matrix elements of the k-th layer, and For the in-plane CTE of the k-th layer, and Let be the coordinates of the bottom and top surfaces of the k-th layer. By optimizing the above formula (using the formulation of each gradient layer as the design variable and minimizing the von Mises equivalent stress at the interface as the objective function), the gradient formulation combination that minimizes the overall thermal stress can be obtained.
[0114] The formula for calculating the von Mises equivalent stress at each interface is as follows:
[0115] ;
[0116] Through gradient structure design, the peak von Mises equivalent stress at each interface is reduced from 120 to 180 MPa in the traditional single adhesive layer scheme to 25 to 45 MPa, a reduction of more than 70%.
[0117] In one alternative implementation, the gradient layers are applied sequentially, starting with the gradient layer closest to the bonding surface. After each layer is applied, it is pre-cured at 80°C to 100°C for 15 to 30 minutes to allow the layer to reach stage B (prepolymer gel state, degree of curing ξ = 0.3 to 0.5), possessing sufficient shape retention but not yet fully cross-linked, thus preserving reactivity for subsequent interlayer interdiffusion.
[0118] After all gradient layers have been pre-cured, the mixture is kept at 110°C for 10 to 20 minutes to allow uncrosslinked components at the interface of adjacent layers to undergo molecular diffusion, forming a 3 to 5 μm component gradient transition zone. (Interdiffusion depth) It can be estimated using Fick's second law:
[0119] ;
[0120] in, The effective diffusion coefficient (related to temperature and degree of curing). The holding time was used. Differential scanning calorimetry (DSC) experiments were conducted to calibrate the holding time at different temperatures and degrees of cure. The value allows for precise control of the interdiffusion depth.
[0121] Optionally, after all gradient layers have completed interdiffusion, the final co-curing stage with programmed temperature control is entered to perform layer-by-layer co-curing treatment on the formed adhesive layer. For example, the curing temperature curve adopts a segmented heating-holding strategy: First holding stage: 120℃ for 60 min, mainly completing the first stage of the aluminum phosphate dehydration condensation reaction (corresponding to a curing degree ξ increasing from 0.5 to 0.7). In this stage, the reaction rate is mild, and chemical shrinkage stress accumulates slowly. Second holding stage: 160℃ for 90 min, mainly completing the deep curing of the PO-Al crosslinking network (corresponding to a curing degree ξ increasing from 0.7 to 0.9). In this stage, the heating rate needs to be controlled to not exceed 2℃ / min to avoid uneven curing caused by temperature gradients. Third holding stage: 200℃ for 60 min (optional, suitable for applications with high heat resistance requirements), completing the complete crosslinking of residual active groups (curing degree ξ greater than 0.95). Cooling stage: Slowly cooling from the highest holding temperature to room temperature at a rate not exceeding 1℃ / min. The purpose of slow cooling is to allow sufficient time for the thermal stress inside the material to be released through viscoelastic relaxation.
[0122] In one alternative implementation, after the adhesive layer is formed, the curing degree of the formed adhesive layer is tested. If it meets the requirements, the next step is carried out; if it does not meet the requirements, the curing process is carried out again until the formed adhesive layer meets the curing degree requirements.
[0123] Step 108: Cover the adhesive layer with the second substrate to form a composite adhesive structure.
[0124] In this process, after all gradient layers have been coated and pre-cured, the second substrate is placed over the upper surface of the adhesive layer, forming a composite adhesive structure with a three-layer sandwich structure consisting of the first substrate, the adhesive layer, and the second substrate. For example, the second substrate is placed gently on the outermost surface of the adhesive layer (i.e., the side furthest from the first substrate) with the bonding surface facing down. To ensure parallelism between the two substrate layers and uniformity of the adhesive layer thickness, a precision pressing device (such as a pneumatic press or vacuum laminator) can be used to apply a uniform pressure of 0.1–0.5 MPa for a pressing time of 10–30 seconds. Air bubbles or relative slippage should be avoided during the pressing process.
[0125] The ceramic matrix phase includes aluminum phosphate, or the ceramic matrix phase includes aluminum phosphate and alumina; the nanofiller regulating phase includes at least two of nano-aluminum nitride, nano-boron nitride and nano-silica; the fiber reinforcing phase includes at least one of chopped carbon fibers and chopped alumina fibers.
[0126] In this system, the ceramic matrix phase provides a continuous network and basic mechanical support; the nanofiller-regulated phase reduces CTE and improves thermal conductivity through a high filling ratio; and the fiber-reinforced phase dissipates fracture energy through bridging and pull-out mechanisms. In one alternative implementation, an aluminum phosphate-alumina composite ceramic is used as the matrix system, with nano-aluminum nitride, nano-boron nitride, and nano-silica particles as CTE-regulated phases, and chopped carbon fibers and chopped alumina fibers as stress-dispersing reinforcement phases. Through multi-level proportioning design, a stepped CTE matching is achieved at the diamond-silicon-ceramic-metal multi-interface, ultimately obtaining a composite adhesive material system that combines low thermal stress, high thermal conductivity, high bond strength, and long-term service reliability.
[0127] In the gradient curing process of the aforementioned adhesive material, the final adhesive layer has a continuously or stepwise varying coefficient of thermal expansion in the thickness direction. This ensures that the coefficient of thermal expansion of the adhesive layer near the first substrate matches the first substrate well, the coefficient of thermal expansion near the second substrate matches the second substrate well, and the intermediate layers achieve a smooth transition. This significantly reduces abrupt changes in the coefficient of thermal expansion between adjacent layers, significantly reduces interfacial thermal stress, effectively suppresses adhesive layer cracking, chip warpage, and device failure caused by thermal cycling, and significantly improves the thermal cycling reliability and service life of heterogeneous material packaging structures. By layer-by-layer coating, pre-curing treatment, and the formation of transition zones, the interlayer interfaces are eliminated while maintaining the orderly construction of the multi-layer gradient structure, achieving a quasi-continuous transition of composition and performance, thereby significantly reducing thermal stress and improving structural reliability. The ceramic matrix phase includes aluminum phosphate or a combination of aluminum phosphate and alumina. This ceramic matrix can be cured at a lower temperature, avoiding damage to heat-sensitive components. Meanwhile, the nano-aluminum nitride and nano-boron nitride in the nanofiller-controlled phase possess high intrinsic thermal conductivity, while the short-cut carbon fibers in the fiber-reinforced phase also exhibit excellent thermal conductivity. The synergistic effect of these two components gives the adhesive layer good thermal conductivity in the thickness direction, which is beneficial for rapidly dissipating heat generated during chip operation, reducing junction temperature, and extending device lifespan. Through a gradient-ratio three-phase composite adhesive layer design, flexible matching of the coefficient of thermal expansion in a multi-interface system is achieved, while also considering low stress, high thermal conductivity, high toughness, and low-temperature process compatibility with sensitive components. This provides an effective technical solution for the packaging of high-reliability quantum sensors and other heterogeneous integrated devices.
[0128] In an exemplary embodiment, the process further includes: applying any layer of slurry using a doctor blade, or applying the slurry placed at the center of the interface of the first substrate radially under centrifugal force by rotational coating.
[0129] In an alternative implementation, prior to step 104, the process further includes pretreatment of the fiber-reinforced phase material. It is understood that in this embodiment, the effective coefficient of thermal expansion of the composite material is further reduced by the low or negative CTE characteristics of the fibers themselves; the fracture toughness of the ceramic matrix composite material is significantly improved through fiber bridging, pull-out, and crack deflection mechanisms, preventing catastrophic propagation of thermal stress cracks.
[0130] For example, for chopped fibers, surface oxidation and coating treatment are required before use. The specific implementation includes: first, oxidation treatment at 400℃ in air for 30 minutes to remove the surface sizing agent and introduce oxygen-containing functional groups; then, deposition of a SiC interface layer approximately 50 to 100 nm thick in a chemical vapor deposition (CVD) furnace. The functions of the SiC interface layer are: first, to protect the chopped fibers from acidic environment corrosion during aluminum phosphate curing; second, to regulate the fiber / matrix interface bonding strength to a moderate level (interfacial shear strength 20 to 40 MPa), enabling the fibers to debond and pull out when cracks propagate to the interface, thereby dissipating a large amount of fracture energy; and third, to increase the CTE of SiC (approximately 4.3 × 10⁻⁶). -6 ( / ℃) is located between the chopped fiber and the matrix, and plays a role in CTE transition, reducing the thermal mismatch stress at the fiber / matrix interface.
[0131] In practical implementation, controlling fiber orientation is crucial for the isotropic or anisotropic design of the CTE within the adhesive layer. This embodiment provides two orientation control schemes:
[0132] Option 1 is the shear-induced orientation method, suitable for scenarios requiring low CTE in a single in-plane direction. A fiber-containing slurry is applied using a doctor blade with a specific gap (gap height 1.2 to 1.5 times the adhesive layer thickness). The shear flow field during the application causes the short fibers to orient themselves along the application direction. The degree of shear-induced orientation is measured using the Herman orientation factor. Characterization:
[0133] ;
[0134] in, The angle between the fiber axis and the coating direction. This is the average of the squared cosines of the directions of all fibers. When Time indicates complete orientation. The time indicates complete randomness. This embodiment achieves this by controlling the slurry viscosity (5 to 20 Pa·s) and the coating speed (10 to 50 mm / s). Fiber orientation in the range of 0.6 to 0.85.
[0135] Option 2 is spin coating, suitable for scenarios requiring in-plane isotropic low CTE. The fiber-containing slurry is placed in the center of the substrate surface, and spin coating causes the slurry to spread radially under centrifugal force, resulting in a random in-plane orientation of the fibers within the rotating flow field. The rotation speed is controlled between 500 and 2000 rpm, and the spin coating time is 10 to 30 seconds.
[0136] Understandably, the quantitative description of the fiber toughening effect uses a crack bridging stress model. When a crack in the matrix propagates to the fiber location, the fiber crossing the crack surface generates a bridging closing force, with the equivalent bridging stress being:
[0137] ;
[0138] in, This refers to the frictional shear stress at the fiber / matrix interface. This is the critical length of the fiber. For crack opening displacement, Where is the fiber pull-out length. The effective increase in fracture toughness of the composite material is:
[0139] ;
[0140] Through the fiber-reinforced design described above, the fracture toughness (KIC) of the ceramic matrix composite adhesive material in this embodiment is increased from 0.8 to 1.2 MPa·m compared to the pure ceramic matrix. 1 / 2 Increased to 3.5 to 5.0 MPa·m 1 / 2 The increase was more than three times.
[0141] In this embodiment, the short-cut carbon fibers and short-cut alumina fibers in the fiber reinforcement phase are uniformly distributed in the ceramic matrix. When the adhesive layer is subjected to thermal stress or external force, the fibers can consume fracture energy through various toughening mechanisms such as crack bridging, fiber pull-out, and crack deflection, which significantly improves the fracture toughness of the adhesive layer and prevents the catastrophic propagation of microcracks, thereby improving the damage tolerance and crack resistance of the material under extreme temperature shock conditions.
[0142] In an exemplary embodiment, prior to step 104, the process further includes: ultrasonically dispersing nano-aluminum nitride in anhydrous ethanol, adding a silane coupling agent and subjecting the mixture to heating, stirring, and reflux treatment, followed by centrifugal washing and vacuum drying to obtain surface-modified nano-aluminum nitride; or,
[0143] Nano-sized boron nitride is oxidized in concentrated nitric acid to introduce oxygen-containing functional groups onto its surface; then, the oxidized boron nitride is coated with a dopamine-inspired coating in an alkaline buffer solution to form a polydopamine surface-modified layer, thus obtaining surface-modified boron nitride nano-nitride; or...
[0144] Nano-silica was dispersed in an organic solvent, and an aluminate coupling agent was added. The mixture was then heated and stirred to react. After filtration and drying, surface-modified nano-silica was obtained.
[0145] The uniform dispersion of high-volume-fraction nanofillers is a key technological challenge in this embodiment. Different surface modification schemes were designed to address the varying surface chemical properties of the three types of nanoparticles.
[0146] For nano-AlN particles, their surface is prone to hydrolysis in humid environments to form aluminum hydroxide (AlOOH), leading to a decline in thermal conductivity and poor dispersibility. In this embodiment, the surface of these particles is modified by coating them with the silane coupling agent KH-560 (γ-glycidoxypropyltrimethoxysilane). The modification process is as follows: nano-AlN powder is ultrasonically dispersed in anhydrous ethanol for 30 min, then 2-4 wt% of KH-560 coupling agent is added. The mixture is stirred and refluxed at 70°C for 4 h, followed by centrifugation and washing, and then vacuum dried at 80°C for 12 h. The epoxy groups on the surface of the modified AlN particles can undergo ring-opening reactions with the P-OH groups in the aluminum phosphate matrix, forming a chemically bonded interface.
[0147] For nano-BN particles, their surface chemical inertness is extremely strong, resulting in poor wettability with most substrates. This embodiment employs a two-step modification method: first, oxidation treatment in concentrated nitric acid (65wt%) at 80°C for 2 hours introduces oxygen-containing functional groups (-OH, -COOH) onto the BN particle surface; subsequently, biomimetic coating with dopamine (DA) in Tris buffer at pH 8.5 is performed, followed by stirring at room temperature for 24 hours to form a polydopamine (PDA) layer approximately 5 nm thick. The abundant catechol and amino groups on the PDA layer can interact multiple times with the aluminum phosphate matrix and fiber surface, while the flexible nature of the PDA layer provides a stress buffer between the nano-BN and the substrate.
[0148] For nano-SiO2 particles, surface modification was performed using the naturally abundant silanol groups (Si-OH) on their surface, employing the aluminate coupling agent DL-411. Nano-SiO2 was dispersed in isopropanol, and DL-411 (3-5 wt% of SiO2 mass) was added. The mixture was stirred at 60°C for 3 hours, then filtered and dried. The aluminate groups on the surface of the modified SiO2 particles can form Al-OP bridging bonds with the aluminum phosphate matrix, significantly improving the interfacial bonding strength.
[0149] In an exemplary embodiment, the step of preparing any kind of slurry includes: obtaining a corresponding precursor solution, nanofiller, and fiber material according to the material ratio corresponding to the current target value of thermal expansion coefficient; performing dry mixing treatment on the nanofiller to obtain a pre-dispersed powder; mixing the pre-dispersed powder into the precursor solution and dispersing it by wet ball milling to obtain a ball-milled slurry; performing vacuum stirring and degassing on the ball-milled slurry to obtain a matrix slurry; adding fiber material to the matrix slurry and performing stirring and vacuum degassing treatment in sequence to obtain the prepared slurry.
[0150] The dispersion of nanofillers in the ceramic matrix employs a three-step process: dry mixing, wet milling, and vacuum degassing. In one optional implementation, the first step involves weighing the three modified nanoparticles according to the designed ratio and dry mixing them at 300 rpm for 2 hours in a planetary ball mill to achieve macroscopic pre-dispersion. The second step involves adding the pre-dispersion powder to a ball mill jar containing an aluminum phosphate precursor solution (using zirconia balls as the grinding medium, with a ball-to-particle ratio of 4:1) and wet ball milling at 400 rpm for 8 to 12 hours to achieve nanoscale dispersion of the nanoparticles in the liquid matrix (characterized by dynamic light scattering (DLS), the particle size distribution D90 after dispersion is less than 100 nm). The third step involves transferring the ball-milled slurry to a vacuum stirrer and degassing it at 100 rpm under a vacuum of -0.095 MPa for 30 minutes, reducing the residual bubble rate in the slurry to below 0.5 vol%.
[0151] It is important to note that the fiber reinforcement phase does not participate in the aforementioned "dry mixing-wet milling-vacuum degassing" ball milling process. This is to avoid mechanical breakage, aspect ratio loss, and peeling of the surface SiC coating caused by the high-energy impact of the zirconia ball milling media on the chopped carbon fibers and alumina fibers. The chopped fibers, after surface oxidation and SiC interface coating treatment, are added to the matrix slurry containing nanofillers after vacuum degassing, according to the designed volume fraction (carbon fibers and alumina fibers are pre-mixed in a set ratio). A rotation-revolution low-shear mixer is used to stir at 100 to 200 rpm for 10 to 20 minutes to ensure uniform fiber distribution in the slurry and an aspect ratio retention rate of not less than 85%. After the fibers are added and stirred evenly, a short (10 minutes) vacuum degassing process is performed again to remove microbubbles entrained during fiber addition. The final "matrix-nanofiller-fiber" three-phase composite slurry is the coating material for each gradient layer.
[0152] In one optional implementation, after mixing the pre-dispersed powder into the precursor solution and dispersing it using wet ball milling to obtain a ball-milled slurry, or after adding fiber material to the matrix slurry and sequentially performing stirring and vacuum degassing to obtain a prepared slurry, the slurry is subjected to a dispersion uniformity test. If the test passes, subsequent steps are performed; if the test fails, the current step is repeated until the dispersion uniformity test passes. Optionally, the quantitative evaluation of dispersion uniformity is performed using microscopic image analysis. On the cross-sectional SEM image of the slurry after coating and curing, the field of view is divided into several equal-area grids, the area ratio of nanoparticles in each grid is statistically analyzed, and the coefficient of variation (CV) is calculated.
[0153] ;
[0154] in, Let be the area fraction of the nanofiller in the i-th grid. Let N be the average area fraction of all grid cells, and N be the total number of grid cells. This embodiment requires the dispersion uniformity CV value to be no more than 15%, preferably no more than 10%.
[0155] In one exemplary embodiment, the ceramic matrix phase comprises aluminum phosphate and alumina; the mass percentage of aluminum phosphate in the ceramic matrix phase is 35%~45%, and the mass percentage of alumina is 55%~65%; the nanofiller regulating phase comprises nano-aluminum nitride, nano-boron nitride, and nano-silica; the volume percentage of nano-aluminum nitride in the nanofiller regulating phase is 35%~65%, the volume percentage of nano-boron nitride is 20%~35%, and the volume percentage of nano-silica is 15%~30%; the fiber reinforcing phase comprises chopped carbon fibers and chopped alumina fibers; the volume percentage of chopped carbon fibers in the fiber reinforcing phase is 60%~75%, and the volume percentage of chopped alumina fibers is 25%~40%; wherein, in each slurry, the volume percentage of the nanofiller regulating phase is 30%~55%, and the volume percentage of the fiber reinforcing phase is 5%~15%.
[0156] In this embodiment, the adhesive material system consists of three main functional components: a ceramic matrix phase, a nanofiller regulating phase, and a fiber reinforcement phase. The synergistic relationship among the three is shown in the attached figure. Figure 4 As shown.
[0157] The ceramic matrix phase uses a composite system of aluminum phosphate (AlPO4) and alumina (α-Al2O3). Aluminum phosphate acts as a low-temperature binder, providing interfacial adhesion, while α-Al2O3 acts as a framework phase, providing structural stiffness. The mass ratio of the two is controlled within the range of (35 to 45) to (55 to 65). Aluminum phosphate was chosen because its curing temperature can be controlled within the range of 150℃ to 250℃, far lower than the silver sintering process temperature, thus avoiding thermal damage to the NV color core. Furthermore, the PO-Al bonded network formed after aluminum phosphate curing exhibits excellent high-temperature stability and resistance to damp heat. The CTE of the matrix phase is approximately 5.5 × 10⁻⁶. -6 / ℃ to 7.0×10 -6 / ℃, between silicon (2.6×10 -6 / ℃) and aluminum nitride ceramics (4.5×10 -6 Between 200°C and 200°C, there is room for further downward adjustment. It is understandable that α-Al₂O₃ constitutes the matrix framework phase with a relatively high mass percentage of 55-65 wt%, providing high elastic modulus, chemical inertness, and thermal stability, but it basically does not participate in chemical reactions below 200°C. AlPO₄ constitutes the reactive and binder phase of the matrix with a mass percentage of 35-45 wt%, and is the dominant component in curing reactions (dehydration condensation, P-O-Al crosslinking), interfacial chemical bonding (Al-O-P bridging), as well as curing shrinkage and stress relaxation response. Therefore, while α-Al₂O₃ is the main component of the matrix in terms of mass composition, AlPO₄ dominates in terms of chemical reactions, interfacial bonding, and stress evolution.
[0158] The nanofiller-controlled phase consists of three types of nanoparticles in different proportions: nano-aluminum nitride (AlN, particle size 20–50 nm), nano-boron nitride (BN, particle size 30–80 nm), and nano-silica (SiO2, particle size 10–30 nm). The physical properties of the three nanofillers each have their own emphasis: the CTE of nano-AlN is approximately 4.5 × 10⁻⁶. -6 With a temperature of / ℃ and a thermal conductivity as high as 320 W / (m·K), it is a core component that balances CTE matching and thermal conductivity; nano-BN has a unique layered structure and extremely low in-plane CTE (approximately -2.7 × 10⁻⁶). -6 The CTE of nano-SiO2 is approximately 0.5 × 10⁻⁶ °C, which can be used as a negative CTE control component to achieve ultra-low expansion design. Furthermore, its interlayer slip properties help release local shear stress. -6 The temperature is close to that of diamond, and the surface is rich in silanol groups, which is conducive to forming chemical bonds with the aluminum phosphate matrix and improving interfacial compatibility. The total volume fraction of the nanofiller is controlled in the range of 30 vol% to 55 vol%, and the volume ratio of the three nanoparticles is AlN to BN to SiO2 equal to (35 to 65) to (20 to 35) to (15 to 30).
[0159] The fiber reinforcement phase is a mixture of chopped carbon fibers (7 μm in diameter, aspect ratio 10 to 30) and chopped alumina fibers (3 to 5 μm in diameter, aspect ratio 15 to 40). The carbon fiber CTE along the axial direction is negative (approximately -0.5 × 10⁻⁶). -6 The carbon fiber volume ratio (CTE) can be further reduced to 230 GPa, while providing mechanical reinforcement with a high elastic modulus (230 GPa). Alumina fibers provide high-temperature chemical inertness and good chemical compatibility with the ceramic matrix. The total fiber volume ratio is controlled within the range of 5 vol% to 15 vol%, and the volume ratio of carbon fiber to alumina fiber is (60 to 75) to (25 to 40).
[0160] As an example, the volume percentage of the nanofiller-controlled phase in each slurry can be 30%, 35%, 40%, 45%, 50%, 55%, or any value within the range of any two of the above points.
[0161] As an example, the volume percentage of the fiber-reinforcing phase in each slurry can be 5%, 10%, 15%, or any value within the range of any two of the above points.
[0162] As an example, the mass percentage of aluminum phosphate in the ceramic matrix phase can be 35%, 40%, 45%, or any value within the range of any two of the above points.
[0163] As an example, the mass percentage of alumina in the ceramic matrix phase can be 55%, 60%, 65%, or any value within the range of any two of the above points.
[0164] As an example, the volume percentage of nano-aluminum nitride in the nanofiller-controlled phase can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, or any value within the range of any two of the above points.
[0165] As an example, the volume percentage of boron nitride nanoparticles in the nanofiller-controlled phase can be 20%, 25%, 30%, 35%, or any value within the range of any two of the above points.
[0166] As an example, the volume percentage of nano-silica in the nanofiller-controlled phase can be 15%, 20%, 25%, 30%, or any value within the range of any two of the above points.
[0167] As an example, the volume percentage of short-cut carbon fibers in the fiber-reinforced phase can be 60%, 65%, 70%, 75%, or any value within the range of any two of the above points.
[0168] As an example, the volume percentage of short-cut alumina fibers in the fiber-reinforced phase can be 25%, 30%, 35%, 40%, or any value within the range of any two of the above points.
[0169] In an exemplary embodiment, the first substrate includes any one of a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer. Before step 106, the process further includes: electrochemically washing the interface of the metal base layer to remove oil, and then anodizing it in an acidic solution to form an oxide layer with a microporous structure, thereby obtaining a pretreated metal base layer; or...
[0170] The interface of the ceramic substrate layer is sandblasted to obtain a pretreated ceramic substrate layer; or...
[0171] A silanol layer is formed at the interface of the silicon chip layer, and a self-assembled monolayer is coated thereon to obtain a pretreated silicon chip layer; or,
[0172] The interface of the diamond layer is treated with oxygen plasma to introduce oxygen-containing functional groups into the interface of the diamond layer, resulting in a pretreated diamond layer.
[0173] In addition to optimizing the material composition design and curing process, this embodiment also enhances the interfacial bonding strength through surface pretreatment of the bonded surfaces.
[0174] For the surface of the metal base layer: firstly, the oil is removed by electrochemical alkaline washing, followed by anodizing in a phosphoric acid-chromic acid solution to form a microporous oxide layer of about 2 to 5 μm thickness. The microporous structure provides a mechanical anchoring effect for the adhesive.
[0175] For the surface of the ceramic substrate layer: sandblasting (80 mesh Al2O3 sand particles, pressure 0.3MPa) is used to form a surface roughness of Ra=1 to 3μm, increasing the mechanical interlocking area, followed by ultrasonic cleaning and drying.
[0176] For the surface of the silicon chip layer: first, Piranha solution cleaning (H2SO4 to H2O2 equals 3 to 1, 80℃, 20min) is performed to generate a hydrophilic silanol layer, and then a layer of APTES (3-aminopropyltriethoxysilane) self-assembled monolayer with a thickness of about 10nm is coated to provide chemical anchoring points for the aluminum phosphate matrix.
[0177] For the surface of the diamond layer: oxygen plasma treatment (power 200W, O2 flow rate 50sccm, treatment time 5min) was used to introduce oxygen-containing functional groups such as CO and C=O onto the diamond surface, reducing its surface energy from approximately 35mJ / m 2 Increased to 65 to 75 mJ / m 2 The contact angle with the aluminum phosphate matrix decreased from greater than 70° to less than 20°.
[0178] After the above surface pretreatment, the shear bond strength test results of each interface are as follows: diamond / adhesive layer interface not less than 12MPa, silicon / adhesive layer interface not less than 15MPa, ceramic substrate / adhesive layer interface not less than 18MPa, metal base / adhesive layer interface not less than 20MPa. All of them meet the reliability requirement that the shear strength retention rate of the quantum current sensor is not less than 80% after 1000 thermal cycles from -40℃ to 85℃.
[0179] It should be understood that although the steps in the flowcharts of the embodiments described above are shown sequentially according to the arrows, these steps are not necessarily executed in the order indicated by the arrows. Unless explicitly stated herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders. Moreover, at least some steps in the flowcharts of the embodiments described above may include multiple steps or multiple stages. These steps or stages are not necessarily completed at the same time, but can be executed at different times. The execution order of these steps or stages is not necessarily sequential, but can be performed alternately or in turn with other steps or at least some of the steps or stages in other steps. It is understood that the steps in different embodiments can be freely combined as needed, and all non-contradictory solutions formed by such combinations are within the scope of protection of this application.
[0180] In one exemplary embodiment, this application also provides an adhesive material for packaging quantum current sensors, the adhesive material comprising a ceramic matrix phase, a nanofiller regulating phase, and a fiber-reinforced phase;
[0181] The ceramic matrix phase includes aluminum phosphate and alumina; the mass percentage of aluminum phosphate in the ceramic matrix phase is 35%~45%, and the mass percentage of alumina is 55%~65%.
[0182] The nanofiller regulating phase includes nano-aluminum nitride, nano-boron nitride, and nano-silica; the volume percentage of nano-aluminum nitride in the nanofiller regulating phase is 35%~65%, the volume percentage of nano-boron nitride is 20%~35%, and the volume percentage of nano-silica is 15%~30%.
[0183] The fiber-reinforcing phase includes chopped carbon fibers and chopped alumina fibers; the volume percentage of chopped carbon fibers in the fiber-reinforcing phase is 60%~75%, and the volume percentage of chopped alumina fibers is 25%~40%.
[0184] In each slurry, the volume percentage of the nanofiller-controlled phase is 30% to 55%, and the volume percentage of the fiber-reinforced phase is 5% to 15%.
[0185] As an example, the volume percentage of the nanofiller-controlled phase in each slurry can be 30%, 35%, 40%, 45%, 50%, 55%, or any value within the range of any two of the above points.
[0186] As an example, the volume percentage of the fiber-reinforcing phase in each slurry can be 5%, 10%, 15%, or any value within the range of any two of the above points.
[0187] As an example, the mass percentage of aluminum phosphate in the ceramic matrix phase can be 35%, 40%, 45%, or any value within the range of any two of the above points.
[0188] As an example, the mass percentage of alumina in the ceramic matrix phase can be 55%, 60%, 65%, or any value within the range of any two of the above points.
[0189] As an example, the volume percentage of nano-aluminum nitride in the nanofiller-controlled phase can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, or any value within the range of any two of the above points.
[0190] As an example, the volume percentage of boron nitride nanoparticles in the nanofiller-controlled phase can be 20%, 25%, 30%, 35%, or any value within the range of any two of the above points.
[0191] As an example, the volume percentage of nano-silica in the nanofiller-controlled phase can be 15%, 20%, 25%, 30%, or any value within the range of any two of the above points.
[0192] As an example, the volume percentage of short-cut carbon fibers in the fiber-reinforced phase can be 60%, 65%, 70%, 75%, or any value within the range of any two of the above points.
[0193] As an example, the volume percentage of short-cut alumina fibers in the fiber-reinforced phase can be 25%, 30%, 35%, 40%, or any value within the range of any two of the above points.
[0194] This embodiment relates to an adhesive material for quantum current sensor encapsulation. Specifically, this adhesive material is a ceramic matrix composite low-thermal-stress adhesive material synergistically reinforced with nanofillers and fibers. Its composition includes a ceramic matrix phase, a nanofiller regulating phase, and a fiber-reinforcing phase. The term "encapsulation-oriented for quantum current sensors" refers to the adhesive material's design specifically for the unique requirements of quantum current sensors during the encapsulation process. Quantum current sensors typically undergo a wide temperature range cycling from extremely low temperatures to room temperature or even higher during operation. Significant thermal expansion coefficient mismatches exist between the layers within the encapsulation structure, easily generating thermal stress at the interfaces, leading to sensor performance drift, increased noise, and even structural failure. The adhesive material in this embodiment provides high mechanical strength and thermal stability through the ceramic matrix phase, precisely adjusts the thermal expansion coefficient of the entire composite material and improves its thermal conductivity through the nanofiller regulating phase, and enhances the material's fracture toughness and thermal shock resistance. The synergistic effect of these three components enables the adhesive material to achieve a gradient match of thermal expansion coefficients with the substrate in the quantum current sensor, thereby significantly reducing interfacial thermal stress during wide-temperature cycling and ensuring the long-term stability and measurement accuracy of the sensor.
[0195] In one exemplary embodiment, this application also provides a sensor, including a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer;
[0196] A composite bonding structure formed by the process described in any of the above embodiments is provided between the metal base layer and the ceramic substrate layer, between the ceramic substrate layer and the silicon chip layer, and between the silicon chip layer and the diamond layer.
[0197] In the composite bonding structure, the first substrate and the second substrate correspond to one of the two adjacent layers of the sensor, respectively.
[0198] In one exemplary embodiment, this application also provides a method for fabricating a sensor, comprising:
[0199] It provides a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer;
[0200] Using the gradient curing process of the adhesive material described in any of the above embodiments, adhesive layers are formed between the metal base layer and the ceramic substrate layer, between the ceramic substrate layer and the silicon chip layer, and between the silicon chip layer and the diamond layer, respectively, to obtain a sensor that is connected as a whole.
[0201] In an exemplary embodiment, the method further includes: performing a layer-level co-curing process on the formed adhesive layer after forming any one adhesive layer; or, performing a component-level co-curing process on all formed adhesive layers after forming all adhesive layers.
[0202] In one alternative implementation, refer to Figure 5 The gradient curing process of the adhesive material includes the following steps: surface modification of nanofillers, pretreatment of chopped fibers, and preparation of ceramic matrix precursors; dry mixing of nanofillers according to multi-level proportions; wet ball milling dispersion of pre-dispersed powder and precursor solution; vacuum stirring and degassing; addition of chopped fibers and stirring and vacuum degassing; preparation of multiple slurries according to slurry gradients; surface pretreatment of the substrate; layer-by-layer coating (spin coating / spin coating) and pre-curing; inter-layer component interdiffusion control; and overall gradient co-curing. The sensor fabrication method includes: following the aforementioned gradient curing process of the adhesive material, after forming an adhesive layer between all adjacent layers, obtaining the final sensor assembly. The gradient curing process of the adhesive material also includes dispersion uniformity testing (CV < 15%) and degree of curing testing to prepare a composite adhesive structure that meets the requirements of dispersion uniformity and degree of curing.
[0203] The curing process of the adhesive material directly determines the residual stress level and interfacial bonding quality of the final product. This embodiment designs a gradient curing process that matches the gradient component structure, the process flow of which is attached. Figure 6 As shown.
[0204] The curing reaction of the aluminum phosphate matrix mainly includes two stages: dehydration condensation and cross-linking curing. Its curing kinetics can be described using a modified Kamal autocatalytic model.
[0205] ;
[0206] Where ξ is the degree of curing (0 to 1). and Let be the rate constant, satisfying the Arrhenius equation:
[0207] ;
[0208] In the formula, For frequency factors, For activation energy, The gas constant is... The absolute temperature is given. Since the content and type of nanofillers vary in different gradient layers, their curing kinetic parameters also differ (the functional groups on the filler surface have catalytic or inhibitory effects on the curing reaction). Therefore, it is necessary to calibrate the kinetic parameters for each gradient layer separately.
[0209] For example, refer to Figure 6 The core feature of the curing process in this embodiment is a three-stage process flow of "layer-by-layer coating - step-by-step pre-curing - overall co-curing":
[0210] The first step: Layer-by-layer coating and pre-curing. Starting with the gradient layer closest to the bonding surface, apply each gradient layer of slurry sequentially. After each layer is applied, pre-cur it at 80°C to 100°C for 15 to 30 minutes to allow the layer to reach stage B (prepolymer gel state, degree of curing ξ = 0.3 to 0.5), possessing sufficient shape retention but not yet fully cross-linked, thus preserving reactivity for subsequent interlayer interdiffusion.
[0211] Section Two: Interlayer Interdiffusion Control. After all gradient layers have been pre-cured, they are kept at 110℃ for 10 to 20 minutes to allow uncrosslinked components at the interface of adjacent layers to undergo molecular diffusion, forming a 3 to 5 μm component gradient transition zone. The interdiffusion depth xd can be estimated using Fick's second law:
[0212] ;
[0213] in, The effective diffusion coefficient (related to temperature and degree of curing). The holding time was used. Differential scanning calorimetry (DSC) experiments were conducted to calibrate the holding time at different temperatures and degrees of cure. The value allows for precise control of the interdiffusion depth.
[0214] The third stage: Overall co-curing. After all gradient layers have completed interdiffusion, the final co-curing stage is entered, controlled by a programmed temperature system. The curing temperature profile in this embodiment employs a segmented heating-holding strategy:
[0215] First insulation stage: 120℃ for 60 minutes, mainly to complete the first stage of aluminum phosphate dehydration condensation reaction (corresponding to the degree of curing ξ increasing from 0.5 to 0.7). The reaction rate is mild in this stage and the chemical shrinkage stress accumulates slowly.
[0216] The second heat preservation stage: heat preservation at 160℃ for 90 minutes, mainly to complete the deep curing of the PO-Al cross-linked network (corresponding to the degree of curing ξ increasing from 0.7 to 0.9). During this stage, the heating rate should be controlled to not exceed 2℃ / min to avoid uneven curing caused by temperature gradient.
[0217] Third insulation stage: 200℃ for 60 minutes (optional, suitable for applications with high heat resistance requirements) to complete the thorough cross-linking of residual active groups (curing degree ξ greater than 0.95).
[0218] Cooling phase: The material is slowly cooled from its highest holding temperature to room temperature at a rate not exceeding 1°C / min. The purpose of slow cooling is to allow sufficient time for the internal thermal stresses of the material to be released through viscoelastic relaxation. The stress relaxation behavior of ceramic matrix composites can be described by the generalized Maxwell model:
[0219] ;
[0220] in, For initial stress, Let be the weight factor of the i-th relaxation element. For relaxation time, This represents the proportion of residual stress in equilibrium. Only when the cooling time is much longer than the longest relaxation time... Only then can the residual stress be fully released. Experiments in this embodiment measured the material system within the temperature range of 150℃ to 200℃. The time is approximately 20 to 40 minutes, so a cooling rate of 1℃ / min is designed to ensure sufficient relaxation time at each temperature point.
[0221] Understandably, volume shrinkage during curing is another significant source of residual stress. The chemical shrinkage rate of the aluminum phosphate matrix is approximately 3 to 5 vol%. By introducing high-volume-fraction nanofillers (30 to 55 vol%) and fibers (5 to 15 vol%), the free shrinkage of the matrix is effectively constrained, reducing the overall linear shrinkage rate of the composite material to 0.3 to 0.8%. The relationship between curing shrinkage rate and the volume fraction of each component is as follows:
[0222] ;
[0223] Applying appropriate curing pressure (0.2 to 0.5 MPa) during the curing process helps eliminate residual pores, enhance interlayer bonding, and further suppress curing shrinkage deformation. The pressure is applied via a vacuum hot press, and the pressure value needs to be optimized according to the slurry viscosity and fiber orientation of each gradient layer: too high a pressure will cause fiber deflection and slurry extrusion, while too low a pressure will not effectively eliminate pores.
[0224] It should be noted that the overall co-curing described in this embodiment has two levels of meaning when implemented at the sensor component level:
[0225] Level 1 (Adhesive Layer Co-curing): For a "local gradient adhesive layer" consisting of multiple CTE gradient layers within a single adhesive location, the process flow of "layer-by-layer coating - step-by-step pre-curing - interlayer interdiffusion - programmed co-curing (120℃ / 60min → 160℃ / 90min → optional 200℃ / 60min → slow cooling at 1℃ / min)" ensures that all gradient layers within the adhesive location complete the final cross-linking simultaneously, forming a composite adhesive layer with continuous CTE transition and overall stress balance.
[0226] Level 2 (Component-level Co-curing): Targeted at... Figure 2The quantum current sensor shown has a four-substrate, three-adhesive-layer stacked architecture: diamond, adhesive layer I, silicon chip, adhesive layer II, ceramic substrate, adhesive layer III, and metal base. This embodiment employs a bottom-up, position-by-position lamination assembly sequence. First, all gradient layers of adhesive layer III are coated and pre-cured to stage B (ξ=0.3 to 0.5) on the metal base, and then the ceramic substrate is laminated. Next, adhesive layer II is coated and pre-cured to stage B on the ceramic substrate, and the silicon chip is laminated. Finally, adhesive layer I is coated and pre-cured to stage B on the silicon chip, and then the diamond is laminated. After all three bonding positions are properly laminated, the entire sensor assembly undergoes a final curing process (following the aforementioned 120 / 160 / optional 200℃ holding curve and a slow cooling rate of 1℃ / min) to simultaneously advance the curing degree of the three adhesive layers to ξ>0.95. The advantages of component-level co-curing are: ① avoiding secondary thermal shock when the lower adhesive layer is fully cured before the upper layer is stacked; ② enabling the entire component to relax stress in the same temperature field and during the cooling process, minimizing the accumulation of residual stress at multiple interfaces; ③ ensuring that the chemical reaction progress among the three adhesive layers is consistent in the final state, resulting in uniform performance.
[0227] If a certain bonding position in the above process needs to be completely cured separately due to assembly process constraints, when pressing the upper substrate after cooling, the cured bonding layer should be treated as a rigid substrate, and the pre-curing temperature of the new bonding layer above it should be relaxed accordingly to avoid excessive thermal disturbance to the cured layer.
[0228] Understandably, when the quantum current sensor is operating, the heat generated by the ASIC chip and laser needs to be efficiently conducted to the heat sink through the adhesive layer. Therefore, the thermal conductivity of the adhesive material is also an important design parameter. In this embodiment, the high filling density of nano-AlN (with a thermal conductivity of 320 W / (m·K)) and the high axial thermal conductivity of carbon fiber (approximately 200 W / (m·K)) enable the composite adhesive material to achieve a high level of effective thermal conductivity.
[0229] The effective thermal conductivity of the composite material was calculated using the Bruggeman effective medium model:
[0230] ;
[0231] For fiber-containing systems, the thermal conductivity along the fiber axis is applied using the upper bound of the mixing law:
[0232] ;
[0233] Thermal conductivity perpendicular to the fiber direction is calculated using a harmonic average.
[0234] ;
[0235] Considering the correction for effective thermal conductivity due to interfacial thermal resistance (Kapitza resistance) at the nanoscale, the effective thermal conductivity of the nanoparticles is:
[0236] ;
[0237] in, The thermal resistance of the Kapitza interface (approximately 10) -8 m 2 (on the order of kWh) The diameter of the nanoparticles is [value missing]. For AlN nanoparticles with a particle size of 20 to 50 nm, the effect of interfacial thermal resistance can reduce their effective thermal conductivity by 30% to 50%. Therefore, surface modification is crucial for reducing [the following]. The value is crucial. After chemical bonding is formed at the AlN / matrix interface through KH-560 modification, It can reduce the cost by about 40%.
[0238] In this embodiment, the effective thermal conductivity of each gradient layer composite adhesive material ranges from 8 to 25 W / (m·K). Among them, the gradient layer on the metal base side (high AlN content) has the highest thermal conductivity, approximately 20 to 25 W / (m·K); the gradient layer on the diamond side (high BN content, with lower interlayer thermal conductivity of BN) has approximately 8 to 12 W / (m·K). The equivalent thermal conductivity of the overall laminated structure through thickness is approximately 12 to 18 W / (m·K), which is 3 to 10 times higher than that of traditional epoxy thermally conductive adhesives (1 to 5 W / (m·K)).
[0239] The key technical parameters of the nanofiller-fiber reinforced ceramic matrix composite low thermal stress adhesive material in this embodiment are shown in Table 1.
[0240] Table 1:
[0241]
[0242] According to such Figure 7 The thermal cycling test results shown indicate that after 1000 thermal cycles from -40℃ to 85℃, no cracks or debonding occurred at any interface of the material system in this embodiment, and the bond strength retention rate was not less than 85%. This demonstrates a significant reliability advantage compared to traditional epoxy thermal conductive adhesives (which develop interface cracks after 300 cycles) and pure ceramic-based adhesives (which develop through cracks after 200 cycles).
[0243] In summary, this embodiment employs a multi-pronged strategy of precisely controlling CTE with nanofillers, dispersing stress concentration with fiber reinforcement, achieving flexible matching across multiple interfaces through gradient microstructure design, and controlling residual stress through gradient curing processes. This results in an adhesive material and its gradient curing process for quantum current sensor packaging that combines low thermal stress, high thermal conductivity, high toughness, and long-term reliability. This provides core material and process assurance for the packaging reliability of quantum current sensors in harsh environments across a wide temperature range.
[0244] It is understandable that, through the synergistic ratio control of the three nanofillers (AlN, BN, SiO2) and the orientation design of the short-cut fibers, the effective CTE of the material in this embodiment can reach 1.5 × 10⁻⁶. -6 / ℃ to 8.0×10 -6 Continuous and precise adjustment within a range of / ℃, covering diamond (approximately 1.0 × 10⁻⁶ ℃). -6 / ℃) to copper alloy (approximately 17×10) -6 The required CTE value for the entire intermediate transition range between (°C) and (°C). Compared to traditional epoxy thermal conductive adhesives where the CTE is not adjustable (fixed at 60 to 80 × 10⁻⁶), this is significantly higher. -6 / ℃) or can only be reduced to a limited extent (to 25 to 40×10) -6 In a situation where / ℃), this embodiment realizes the on-demand precise design capability of CTE, providing ample design freedom for thermal stress matching of various heterogeneous material interfaces.
[0245] By designing a gradient component structure, the CTE jump variables of each adjacent interface are controlled within 2 × 10⁻⁶. -6 Within a temperature range of / ℃, and with the formation of a continuous transition zone through interlayer interdiffusion, this embodiment reduces the von Mises equivalent thermal stress at each interface in the diamond-silicon-ceramic-metal multi-interface system from 120 to 180 MPa in traditional single-adhesive-layer solutions to 25 to 45 MPa, a reduction of over 70%. This significant reduction in thermal stress fundamentally eliminates the risk of thermal cycling cracking in the chip adhesive layer, increasing the number of thermal cycles the device can withstand from less than 300 to over 1000, extending the equivalent service life by more than three times.
[0246] The maximum curing temperature of the material system in this embodiment does not exceed 200°C, and the typical curing temperature is 160°C, which is far lower than the 250 to 300°C required for the silver sintering process. This mild curing condition ensures that the zero-phonon line characteristics, coherence time T2, and charge state stability of the diamond NV color center are not affected by the thermal process of the bonding process, thus guaranteeing that the sensitivity performance of the quantum sensor is not degraded by the packaging process.
[0247] Through the synergistic reinforcement of high volume fraction nano-AlN filler and carbon fiber, the composite adhesive material in this embodiment achieves an equivalent thickness-direction thermal conductivity of 12 to 18 W / (m·K), which is 3 to 10 times higher than that of traditional epoxy thermally conductive adhesives (1 to 5 W / (m·K)). This excellent thermal conductivity reduces the chip junction temperature by 15 to 25°C, effectively improving the heat dissipation path of ASIC chips and lasers, and extending the thermal fatigue life of electronic devices.
[0248] Short-cut carbon fibers and alumina fibers synergistically toughen ceramic matrix composite adhesives through multiple mechanisms such as crack bridging, fiber pull-out, and crack deflection, increasing the fracture toughness from 0.8 to 1.2 MPa·m in pure ceramic matrices. 1 / 2 Increased to 3.5 to 5.0 MPa·m 1 / 2 The toughness is improved by more than 3 times. Even if microcracks occasionally initiate under extreme temperature shock conditions, the fiber bridging mechanism can effectively prevent the catastrophic propagation of cracks, significantly improving the material's damage tolerance.
[0249] All the process steps involved in this embodiment, including nanofiller surface modification, planetary ball milling dispersion, spin coating / spin coating film formation, and programmed temperature-controlled curing, can be implemented on an electronic packaging production line without the need for special ultra-high temperature, ultra-high pressure, or ultra-high vacuum equipment. Through standardized process parameter control (temperature ±2℃, pressure ±0.05MPa, time ±1min), the batch-to-batch consistency of material properties can reach less than 10%, demonstrating good adaptability to engineering-scale mass production.
[0250] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this application.
[0251] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.
Claims
1. A gradient curing process for an adhesive material, characterized in that, The process includes: A first substrate and a second substrate are provided; the first substrate and the second substrate are respectively selected from any two of a diamond layer, a silicon chip layer, a ceramic substrate layer and a metal base layer; Multiple slurries with gradient-varying target coefficients of thermal expansion were prepared. Each slurry comprised a ceramic matrix phase, a nanofiller regulating phase, and a fiber-reinforced phase. The material ratios varied in different slurries, and the gradient-varying target coefficients of thermal expansion were determined based on the difference between the thermal expansion coefficients of the first substrate and the second substrate. The adhesive layer contained N sublayers, where N≥2, and the CTE jump between adjacent sublayers did not exceed 2×10⁻⁶. -6 / ℃; Multiple slurries are applied layer by layer in a gradient manner on the interface of the first substrate to form an adhesive layer; wherein, after each layer of slurry is applied, a pre-curing treatment is performed at 80°C to 100°C for 15 to 30 minutes to make the current layer reach a prepolymer gel state with a degree of curing ξ=0.3~0.5; after all gradient layers are applied and pre-cured, the layer is kept at 110°C for 10 to 20 minutes to form a 3 to 5 μm transition zone for component interdiffusion between adjacent layers; The second substrate is covered on the adhesive layer to form a composite adhesive structure; The ceramic matrix phase comprises aluminum phosphate and alumina; the mass percentage of aluminum phosphate in the ceramic matrix phase is 35%~45%, and the mass percentage of alumina is 55%~65%. The nanofiller regulating phase includes nano-aluminum nitride, nano-boron nitride, and nano-silica; the volume percentage of nano-aluminum nitride in the nanofiller regulating phase is 35%~65%, the volume percentage of nano-boron nitride is 20%~35%, and the volume percentage of nano-silica is 15%~30%. The fiber reinforcement phase comprises chopped carbon fibers and chopped alumina fibers; the volume percentage of the chopped carbon fibers in the fiber reinforcement phase is 60%~75%, and the volume percentage of the chopped alumina fibers is 25%~40%. In each slurry, the volume percentage of the nanofiller regulating phase is 30% to 55%, and the volume percentage of the fiber reinforcing phase is 5% to 15%.
2. The process according to claim 1, characterized in that, The process also includes: When applying any layer of slurry, a doctor blade is used for application, or the slurry placed at the center of the interface of the first substrate is radially spread under centrifugal force by rotational coating.
3. The process according to claim 1, characterized in that, The steps for preparing any kind of slurry include: Based on the material ratio corresponding to the current target value of thermal expansion coefficient, obtain the corresponding precursor solution, nanofiller and fiber material; The nanofiller is subjected to dry mixing to obtain a pre-dispersed powder; The pre-dispersed powder is mixed into the precursor solution and dispersed by wet ball milling to obtain a ball mill slurry; The ball-milled slurry was subjected to vacuum stirring and degassing to obtain a matrix slurry; The fiber material is added to the matrix slurry, and the mixture is stirred and vacuum degassed in sequence to obtain the prepared slurry.
4. The process according to claim 1, characterized in that, Before preparing various slurries with target thermal expansion coefficients exhibiting gradient changes, the process further includes: The nano-aluminum nitride was ultrasonically dispersed in anhydrous ethanol, followed by the addition of a silane coupling agent and subsequent heating, stirring, and reflux treatment. After centrifugation, washing, and vacuum drying, surface-modified nano-aluminum nitride was obtained; or... The boron nitride nanoparticles are oxidized in concentrated nitric acid to introduce oxygen-containing functional groups onto their surface; then, in an alkaline buffer solution, the oxidized boron nitride nanoparticles are coated with a dopamine-inspired coating to form a polydopamine surface-modified layer, resulting in surface-modified boron nitride nanoparticles; or... The nano-silica was dispersed in an organic solvent, and an aluminate coupling agent was added. The mixture was then heated and stirred to react. After filtration and drying, the surface-modified nano-silica was obtained.
5. The process according to claim 1, characterized in that, The first substrate includes any one of a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer. Before forming the adhesive layer by coating the various slurries layer by layer at the interface of the first substrate according to a gradient, the process further includes: The interface of the metal base layer is subjected to electrochemical alkaline washing to remove oil, followed by anodizing in an acidic solution to form an oxide layer with a microporous structure, resulting in a pretreated metal base layer; or... The interface of the ceramic substrate layer is sandblasted to obtain a pretreated ceramic substrate layer; or, A silanol layer is formed at the interface of the silicon chip layer, and a self-assembled monolayer is coated thereon to obtain a pretreated silicon chip layer; or, The interface of the diamond layer is treated with oxygen plasma to introduce oxygen-containing functional groups into the interface of the diamond layer, resulting in a pretreated diamond layer.
6. An adhesive material for encapsulating quantum current sensors, characterized in that, The adhesive material comprises a ceramic matrix phase, a nanofiller regulating phase, and a fiber-reinforced phase; The ceramic matrix phase comprises aluminum phosphate and alumina; the mass percentage of aluminum phosphate in the ceramic matrix phase is 35%~45%, and the mass percentage of alumina is 55%~65%. The nanofiller regulating phase includes nano-aluminum nitride, nano-boron nitride, and nano-silica; the volume percentage of nano-aluminum nitride in the nanofiller regulating phase is 35%~65%, the volume percentage of nano-boron nitride is 20%~35%, and the volume percentage of nano-silica is 15%~30%. The fiber reinforcement phase comprises chopped carbon fibers and chopped alumina fibers; the volume percentage of the chopped carbon fibers in the fiber reinforcement phase is 60%~75%, and the volume percentage of the chopped alumina fibers is 25%~40%. In each slurry, the volume percentage of the nanofiller regulating phase is 30% to 55%, and the volume percentage of the fiber reinforcing phase is 5% to 15%. The adhesive material is formed as an adhesive layer, which contains N sublayers, where N≥2, and the CTE jump between adjacent sublayers does not exceed 2×10. -6 / ℃; There is a 3 to 5 μm transition region between adjacent sublayers formed by component interdiffusion; The adhesive layer is prepared by a gradient curing process of the adhesive material as described in any one of claims 1 to 5.
7. A sensor, characterized in that, include: Metal base layer, ceramic substrate layer, silicon chip layer and diamond layer; The composite bonding structure formed by the process described in any one of claims 1 to 5 is respectively provided between the metal base layer and the ceramic substrate layer, between the ceramic substrate layer and the silicon chip layer, and between the silicon chip layer and the diamond layer. In the composite bonding structure, the first substrate and the second substrate correspond to one of the two adjacent layers of the sensor, respectively.
8. A method for manufacturing a sensor, characterized in that, The method includes: It provides a metal base layer, a ceramic substrate layer, a silicon chip layer, and a diamond layer; Using the process described in any one of claims 1 to 5, adhesive layers are formed between the metal base layer and the ceramic substrate layer, between the ceramic substrate layer and the silicon chip layer, and between the silicon chip layer and the diamond layer, respectively, to obtain a sensor that is connected as a whole.
9. The method according to claim 8, characterized in that, The method further includes: After any adhesive layer is formed, the formed adhesive layer is subjected to a layer co-curing treatment; or, After all adhesive layers are formed, all adhesive layers are subjected to component-level co-curing.
Citation Information
Patent Citations
High-temperature-resistant adhesive for bonding sensor and use method of high-temperature-resistant adhesive
CN119039887A
Flip chip bottom filling adhesive as well as preparation method and application thereof
CN120888257A
Preparation method of double-layer high-temperature adhesive for connecting brass and aluminum oxide
CN121160233A